การพัฒนาคุณค่าทางโภชนะของรำสกัดน้ำมันเพื่อเป็นอาหารสัตว์ด้วยยีสต์จากโรงงานผลิตเบียร์ - เบี้ยทอง, วนิดา; ศรีชนะ, ดรุณี (Thai Journal of Science and Technology, 2019)
Abstract The objective of this study was to evaluate the nutritional value and digestibility of defatted rice bran fermented with Brewer’s yeast (BY) at 0, 10, 20 and 30 % for 0, 1, 2, 3 and 4 weeks. The result data concerning nutritional value showed that organic matter (OM) of defatted rice bran fermented with BY for 0-4 weeks was increased (p < 0.05), whereas dry matter (DM) and acid detergent fiber (ADF) of defatted rice bran fermented with BY for 0-4 weeks were decreased (p < 0.05). Defatted rice bran fermented with 30 % BY (2-3 weeks) had highest (p < 0.05) crude protein with the range of 25.03-25.42 % and defatted rice bran fermented with 30 % BY (1-2 weeks) had lowest (p < 0.05) neutral detergent fiber (NDF) with the range of 43.26-43.35 %. The ruminal digestibility (in vitro) of DM (56.97 %) and OM (55.36 %) of defatted rice bran fermented with 30 % BY at 4 weeks were high (p < 0.05). Furthermore, it was found that the DM digestibility in monogastric animal (in vitro) of defatted rice bran fermented with 30 % BY (3-4 weeks) and OM digestibility in monogastric animal of defatted rice bran fermented with 30 % BY (2-4 weeks) were highest (p < 0.05) with the range of 62.63-62.86 and 62.11-62.51 %, respectively. It was concluded that nutritional value of defatted rice bran was increased, whereas ruminal digestibility and digestibility in monogastric animal of defatted rice bran were maximized when fermented with BY at 30 % for 4 weeks. Keywords: defatted rice bran; brewer’s yeast; nutritional value; digestibility